Assessing intercity bus safety performance in Malaysia using a composite safety performance index - Daud, Mohd Shazwan (2016)
In recent years in Malaysia, serious road traffic accidents involving intercity buses have been increasing. Intercity bus drivers are generally at a higher risk for crashes due to long hours of driving and exposure to different road conditions. Therefore, understanding and quantifying their risks and taking steps to manage them could improve intercity bus safety. However, testing intercity bus safety levels through a complete set of road crash risk indicators is difficult to quantify and interpret. In order to avoid this difficulty, it has been recommended that the analysis of intercity bus safety could be tackled by aggregating a multidimensional set of risk indicators into a composite safety performance index (SPI) by giving different weighted importance to different risk domains. However, the development of the composite SPI is sensitive to the choice of weighting method. Given this background, the present work has two objectives. First, to examine the suitability of different weighting methods to develop the composite SPI for intercity buses. Second, to apply SPI values obtained by appropriate weighting method to measure and compare intercity bus safety in terms of risk domains. The risk domains considered in this study are road environment conditions, bus driver driving behaviours and bus safety conditions. A two-stage sampling method was used to choose intercity bus samples. In the first stage, a simple random sampling technique was used to select 30 out of 50 active intercity bus companies in Malaysia. At the second stage of sampling, 30% of the total number of buses were randomly selected from each selected intercity bus company. A correlation analysis of each weighting method ranking and the road crash (RC) ranking was performed to determine which weighting method ranking appropriate for developing the SPI. The paired sample t-test was then applied to the best weighting method to determine which SPI were significantly different from each other. Of the three risk domains, road environment conditions have the highest average weight over the three weighting methods. This implies that an improvement in the road environment could increase the overall safety performance of intercity buses. The results of correlation analysis indicated that the FA method fits the best with the road crash (RC) ranking. The results of paired sample t-test indicated that road environment conditions have contributed more to intercity bus safety risks on the East coast than on the West coast of peninsular Malaysia. The evidence presented in this study reveals that different intercity bus companies showed mixed safety performance in different risk domains. Therefore, we suggest the development of targeted road safety programs for each intercity bus company to address intercity bus safety problems. In sum, the composite SPI can not only be used to identify possible risk management strategies to improve intercity bus safety but also to provide safety information for intercity bus passengers, making them fully aware of bus safety conditions. This, in turn, could place economic pressure on bus operators to improve their vehicles’ safety performance